2017
DOI: 10.1080/02640414.2017.1402552
|View full text |Cite
|
Sign up to set email alerts
|

Movement pattern and physiological response in recreational small-sided football – effect of number of players with a fixed pitch size

Abstract: Recreational soccer is an effective health-promoting activity, but it is unclear how different game formats influence internal and external load. Thus, to be able to advise how to maximise the outcome of recreational football, we examined movement pattern and physiological response in 11 untrained men (32.6 ± 6.7 yrs, 23.3 ± 4.9 fat%, 43.4 ± 5.3 ml·min·kg) during three football sessions comprising 4 × 12 min of 3v3, 5v5 or 7v7 with a constant pitch size of 20 × 40 m. Movement pattern, heart rate (HR), blood la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 27 publications
5
34
3
Order By: Relevance
“…This relatively high post-session blood lactate concentration suggests that walking football places a significant demand on the anaerobic system, in particular the glycolytic pathway, supporting the notion that walking football is a vigorous-intensity exercise for older adults. As expected, the observed concentrations were not as high as previously observed during small-sided recreational football matches in young (early 30's) untrained males (Randers, Nielsen, Bangsbo, & Krustrup, 2014;Randers et al, 2010;Randers, Ørntoft, Hagman, Nielsen, & Krustrup, 2018) but comparable data in older adults is not available. Due to logistical constraints we were unable to measure blood lactate at regular intervals (e.g., every 15 min) during the sessions, which would have allowed us to assess transient changes in blood lactate.…”
Section: Discussionsupporting
confidence: 46%
“…This relatively high post-session blood lactate concentration suggests that walking football places a significant demand on the anaerobic system, in particular the glycolytic pathway, supporting the notion that walking football is a vigorous-intensity exercise for older adults. As expected, the observed concentrations were not as high as previously observed during small-sided recreational football matches in young (early 30's) untrained males (Randers, Nielsen, Bangsbo, & Krustrup, 2014;Randers et al, 2010;Randers, Ørntoft, Hagman, Nielsen, & Krustrup, 2018) but comparable data in older adults is not available. Due to logistical constraints we were unable to measure blood lactate at regular intervals (e.g., every 15 min) during the sessions, which would have allowed us to assess transient changes in blood lactate.…”
Section: Discussionsupporting
confidence: 46%
“…The aerobic intensity during the soccer sessions were moderate-to-high for the male and female patients. As reported by Krustrup 10 and Randers 35 , even with the modification of the rules, pitch size and number of players during small-sided soccer are enough to achieve high-intensity exercise for all participants.…”
Section: Discussionmentioning
confidence: 61%
“… 1 , 2 , 3 , 4 Given the link between training intensity and positive outcomes in cardiovascular, metabolic, and musculoskeletal health, 5 , 6 the high physiological and activity demands underpinning football SSG may be central to their use as a health promotion intervention. 7 Despite the popularity of football SSG, few studies 8 , 9 , 10 , 11 , 12 have identified the influence of game format (e.g. pitch size, team sizes) on the physiological and activity intensities encountered by recreational players.…”
Section: Introductionmentioning
confidence: 99%